The unemployment inflation trade-off in the euro area - Tobias Linzert (Institute for the Study of Labor (IZA), 2005)
This paper analyzes the relationship between unemployment and wage inflation for 10 of the euro area countries. The combination of low wage inflation and high unemployment in Europe is usually attributed to a rise in the natural rate of unemployment. Using a panel data approach, this paper models directly the specific structural determinants of the natural rate of unemployment that may account for a changing pattern in the unemployment inflation trade-off. Moreover, it analyzes whether the responsiveness of wages crucially depends on the level of inflation and the level of unemployment. This allows to detect possible downward rigidity of wages and grease or sand effects of positive levels of inflation.
Keywords: E24; E31; J64; C23; 330; Phillips Curve; unemployment; panel analysis